Smart Phone Application for Drowsiness Detection during Driving - Guksa, Baris; Erkmen, Burcu (IEEE, 2017)
In this study, with the help of the front camera of a smart phone, decreasing the possibility of accident by analysing the state of sleep from the movements of the driver and the car is aimed and a program which informs the driver's relatives via sending them a short message service in case of an accident is worked on. Detection of the speed of the car by using global positioning system and accelerator sensor; at the same time, detection of the possibility an accident due to the sudden speed change by using accelerator sensor can be done. With the designed algorithms, state of sleep of the driver is controlled by perceiving the movement of eyelid from the front camera of the phone. Besides the learnt from eyelid, if the number of blinking is less or more than the normal and if the immotility of the driver is perceived and the speed change read from GPS is more; the driver is given a warning of You're falling asleep!.
Keywords: ALS sensor; gyro and accelerometer sensor; GPS; sleep detection; driver safety; smartphone; application; image processing; Engineering